Detection of yadN, ygiL, and draE Genes in Ciprofloxacin-resistant Uropathogenic Escherichia coli - Ahmed, Suaad Ali; Flayyih, May Talib (Iraqi Journal of Science, 2025)
Background: In Uropathogenic E. coli (UPEC), Yad and Ygi fimbriae are associated with the colonization of the bladder.Methods: A total of 200 urine samples were gathered from Urinary Tract Infection (UTI) patients to isolate Escherichia coli using Hichrome E. coli and Hichrome UTI agar media. Susceptibility of Uropathogenic E. coli isolates to 16 different antibiotics was determined by using the Disc Diffusion Approach and VITEK 2 compact system.  Congo red agar and tissue culture plates were employed for the biofilm development test. By using Polymerase Chain Reaction (PCR) and gel electrophoresis, yadN, ygiL, and draE genes were detected.Results: From 40 bacterial isolates, 21 (52.5%) were resistant to ciprofloxacin. The highest resistance of UPEC isolates was to Ampicillin (34/40; 85%) and Cefazolin (33/40; 82.5%), while the lowest resistance was to Amikacin and Tagicycline (0/40; 0%). However, none of the isolates were found to be extensively drug resistant (XDR) or pandrug-resistant (PDR) according to the VITEK 2 compact system, but 31 out of 40 bacterial isolates (77.5%) were multidrug resistant (MDR). The results of using microtiter plates revealed that (44%) of the isolates formed strong biofilms, while the remaining (14/25; 56%) were moderate biofilm-forming. When tested using the Congo red method, (9/25; 36%) gave black colonies (strong biofilm), (13/25; 52%) gave grey colonies (moderate biofilm), while only three isolates produced pink growth on medium (12%) (non-biofilm producing). The results of PCR showed that out of 22 UPEC isolates, (19/22 ; 86.36%) contained the yadN gene, (13/22; 59.09%) had the ygiL gene, and none had the draE gene.Conclusion: The yadN gene was more frequent in UPEC Isolates, followed by the ygiL gene, which indicates that both have crucial roles in the virulence.